1992
DOI: 10.1128/jvi.66.10.6213-6219.1992
|View full text |Cite
|
Sign up to set email alerts
|

Human immunodeficiency virus type 1 Nef protein inhibits NF-kappa B induction in human T cells

Abstract: We report here that the HIV-1-encoded Nef protein inhibits the induction of NF-KB DNA-binding activity by T-cell mitogens. However, Nef does not affect the DNA-binding activity of other transcription factors implicated in HIV-1 regulation, including SP-1, USF, URS, and NF-AT. Additionally, Nef inhibits the induction of HIV-1and interleukin 2-directed gene * Corresponding author.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

1994
1994
1999
1999

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(41 citation statements)
references
References 34 publications
0
41
0
Order By: Relevance
“…It is also likely that HIV antigens tat, nef, gp120 or other HIV antigens may differentially regulate IL-10 in T cells and monocytes. HIV antigens tat and nef down-regulate the expression of several cellular genes including the cytokine genes [42][43][44]. The role of HIV antigens and/or cytokines in inhibiting IL-10 production by T cells at the transcriptional or post-transcriptional level remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…It is also likely that HIV antigens tat, nef, gp120 or other HIV antigens may differentially regulate IL-10 in T cells and monocytes. HIV antigens tat and nef down-regulate the expression of several cellular genes including the cytokine genes [42][43][44]. The role of HIV antigens and/or cytokines in inhibiting IL-10 production by T cells at the transcriptional or post-transcriptional level remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…68 Contrasting with these results, several reports have suggested that Nef inhibits lymphocyte activation. 55,[69][70][71][72][73][74][75] This latter phenotype was observed for instance in Jurkat cell clones selected for the stable expression of HIV-1 nef or following the acute electroporation of recombinant, nonmyristoylated, Nef protein into human T lymphoid cells. 27 Supporters of the hyperactivation model see in this effect of Nef a way for the virus to create an environment favourable for its own gene expression and propagation.…”
Section: Nef and Signallingmentioning
confidence: 99%
“…These effects of Nef include downregulation of CD4 [102][103][104][105][106] and blockage of TCR-mediated IL-2 production in Jurkat T cells [106,107]. The molecular basis of these effects is not entirely clear but may reflect the ability of Nef to inhibit the activation of NF-κB and/or AP-1 transcription factors [108][109][110] and to associate with cellular serine/threonine kinases [111][112][113][114][115][116][117].…”
Section: Interaction Of Pkcθ With the Hiv Protein Nefmentioning
confidence: 99%